A new species of the genus Paraxantia Liu & Kang, 2009—the first record from Hainan Island, China (Orthoptera: Tettigoniidae) - Wu, Chao; Liu, Chun-Xiang (Zootaxa, 2024)
A new species: Paraxantia jianyuni sp. nov., is described based on six specimens collected in Hainan Island, China, representing the first record of this genus for this large island in southern China. Necessary illustrations and life image of the new species are presented, the distribution of the new species is discussed and mapped.